Wyposażenie polskich gmin w infrastrukturę lokalną w 2004 roku - wyniki badań ilościowych - Goleń, Marek Jakub (The Saturation of Local Infrastructure in Polish Communes in 2004 - the Results of Quantity Research, 2007)
The article presents the results of quantity research aimed at studies of the condition of the commune infrastructure regarding quantity in each Polish commune. The research was carried out on the basis of the public databases (Regional Data Bank and Information Database on Education) in the following components of the commune infrastructure: water-supply systems, sewage systems, sewage treatment plants, local roads, public transport, nursery, primary and secondary schools, community health centres, local libraries, local sports structures. The effects of the research are the maps of the saturation of commune infrastructure in Polish communes on the base of the synthetic tacsonomic measure of the saturation of commune infrastructure in communes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 350-360